Defining Temporally Dynamic Life Cycle Assessment: A Review. (30th January 2020) - Sohn, Joshua; Kalbar, Pradip; Goldstein, Benjamin; Birkved, Morten
ABSTRACT: Durable goods last for years, decades, or even centuries. The environmental implications of the changing social, economic, and material conditions in which these goods are embedded can be overlooked by conventional life cycle assessment (LCA) that assumes a static world. To avoid this oversight, methods such as dynamic LCA (DLCA) are increasingly being used. Despite the growing use of DLCA, numerous questions remain, including how this dynamism is incorporated and what aspects of any given DLCA are dynamic. To answer these questions, we performed a review of 56 DLCAs, of which 44 propose a framework for DLCA covering all International Organization for Standardization phases of an LCA or that carry out a DLCA. Three types of LCA dynamism are identified and assessed for the reviewed literature: dynamic process inventory, dynamic systems, and dynamic characterization, while a further 2 types of LCA dynamism, dynamic scope and dynamic weighting, are proposed but not applied in the assessed literature. We found that the implementation of DLCA varies widely, and inventories accounting for dynamic characteristics are by far the most prevalent expression of DLCA. To reduce confusion surrounding the discussion of DLCA, we propose a definition of DLCA and its subtypes: full DLCA, partial DLCA, and prospective LCA. It is concluded that, among the current array of DLCA definitions, the implementation of partially dynamic LCA (PDLCA), which applies dynamism in only some parts of the LCA, is common and likely to continue. This is because PDLCA offers quantifiable marginal utility in terms of increased validity of the assessment, in relation to conventional LCA methods, but caution is needed in applying PDLCA because of potential for introducing bias into the LCA. To avoid this problem, we propose incorporating system dynamism as part of a sensitivity analysis, particularly in PDLCA that are limited by missing data. Integr Environ Assess Manag 2020;16:314–323. © 2019 SETAC KEY POINTS: The application of dynamism in life cycle assessment varies significantly due to a lack of definition and methodological guidelines. Incorporation of dynamics in a life cycle assessment can significantly alter results. By incorporating dynamism as a type of sensitivity analysis instead of in the reported results, when data are not available to incorporate dynamism in the entire system, inadvertent bias can be avoided while maintaining the benefits of dynamic assessment. We define dynamic life cycle assessment as well as 3 distinct subtypes that were encountered in the literature.